Afghan women's empowerment and antenatal care utilization: a population-based cross-sectional study - Sarah Yeo; Melanie Bell; Yu Ri Kim; Halimatou Alaofè (BMC, 2022)
Abstract Background Although antenatal care (ANC) offers a unique opportunity to diagnose and prevent complications by mitigating modifiable risk, 38.2% of women did not complete any ANC visits in Afghanistan in 2015. Women empowerment is associated with increased use of ANC; however, there is no evidence of the effect of women empowerment on ANC in the country. Addressing this gap, we aimed to evaluate the association between women's empowerment and ANC utilization based on the conceptual framework of women's empowerment. Methods We analyzed data from the 2015 Afghanistan Demographic and Health Survey for 11,056 women. The association between four domains of women's empowerment, including capability, access to resources, security, and decision-making and power, and at least four ANC visits was analyzed using a multivariable logistic regression. Results After adjusting for covariates, access to information (AOR 1.38, 95%CI 1.24, 1.54) and decision-making (AOR 1.16, 95%CI 1.08, 1.24) were positively associated with four or more ANC visits. Compared to those without any education, women with primary education (AOR 1.67, 95%CI 1.02, 2.72), secondary education (AOR 2.43, 95%CI 1.25, 4.70), and higher education (AOR 3.03, 95%CI 1.30, 7.07) had higher odds of least four ANC visits. However, asset ownership was negatively associated with ANC visits (AOR 0.72, 95%CI 0.56, 0.92). Variables related to security and literacy were not associated with the minimum ANC visits. Conclusions The mixed results of the study highlight the complex natures of women's empowerment, warranting a more nuanced understanding of women's empowerment in the context and future research that capture multidimensionality of women's empowerment. Also, efforts to empower women, particularly those with no education and had less decision-making power and access to health information, could be an effective strategy to enhance ANC use in Afghanistan.